HMGB1 blockade differentially impacts pulmonary inflammation and defense responses in poly(I:C)/LPS-exposed heart transplant mice. (August 2016) - Ming, Bingxia; Gao, Ming; Zou, Huijuan; Chen, Huoying; Sun, Yan; Xiao, Yifan; Lai, Lin; Xiong, Ping; Xu, Yong; Tan, Zheng; Wang, Jing; Chen, Gang; et al.
Highlights: HMGB1 was found to be higher in BAL fluids after heart transplantation. The response to poly(I:C)/LPS challenge was aggravated in heart transplant mice. HMGB1 blockade alleviated lung inflammation and maintained defense responses. Effects of HMGB1 blockade on PAMP's response in recipients need further attention. Abstract: A large number of recipients are in a compromised immune defense condition because of the routine application of immunosuppressive regimens after heart transplantation. Our previous work demonstrated that blockade of high-mobility group box 1 (HMGB1) prolongs the graft survival. Whether and how HMGB1 blockade impacts respiratory responses against pathogen-like challenge in organ transplant recipients when it improves cardiac graft are not elucidated. At the present study, after abdominal heterotopic heart transplantation, the recipient mice were treated with HMGB1 mAb, and then challenged with poly(I:C) or LPS intratracheally on day 7 post transplantation. We found that the level of bronchoalveolar lavage (BAL) HMGB1 was elevated after heart transplantation, and aggravated responses to respiratory tract poly(I:C)/LPS challenge were observed. HMGB1 neutralizing mAb treatment in poly(I:C)-challenged recipient mice alleviated pulmonary histopathological changes, neutrophil infiltration and inflammatory cytokine release, but unaffected the level of IFN-β, the distribution of CD11b + CD27 + /CD11b + CD27 − NK cell subsets, and CD8 + T cell responses. In LPS-exposed recipient mice, HMGB1 mAb treatment ameliorated pulmonary inflammatory damage and enhanced the phagocytosis of phagocytic cells. Thus, this study may establish a basis for the application of HMGB1 blockade to improve the outcomes of heart transplant recipients because HMGB1 inhibition ameliorates pulmonary inflammation, but maintains defense-associated responses.